2018
DOI: 10.1016/j.jcmgh.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients in Nonalcoholic Fatty Liver Disease Pathogenesis

Abstract: Micronutrients include electrolytes, minerals, vitamins, and carotenoids, and are required in microgram or milligram quantities for cellular metabolism. The liver plays an important role in micronutrient metabolism and this metabolism often is altered in chronic liver diseases. Here, we review how the liver contributes to micronutrient metabolism; how impaired micronutrient metabolism may be involved in the pathogenesis of nonalcoholic fatty liver disease (NAFLD), a systemic disorder of energy, glucose, and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 137 publications
1
96
0
Order By: Relevance
“…Individuals with obesity may also have less exposure to sunlight due to a relatively sedentary lifestyle, resulting in less vitamin D being produced in the skin. It has also been suggested that obesity-related steatosis of the liver may lead to reduced activation of vitamin D [34]. Recent research has found that the proinflammatory state which comes with obesity may lead to alterations in vitamin D metabolism and lowered circulating levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with obesity may also have less exposure to sunlight due to a relatively sedentary lifestyle, resulting in less vitamin D being produced in the skin. It has also been suggested that obesity-related steatosis of the liver may lead to reduced activation of vitamin D [34]. Recent research has found that the proinflammatory state which comes with obesity may lead to alterations in vitamin D metabolism and lowered circulating levels [35].…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrients are important for the development of NAFLD. To date, the micronutrients involved in NAFLD are zinc, copper, iron, selenium, magnesium, vitamins A, C, D and E and carotenoids . The proposed mechanisms of action are their antioxidant, antifibrotic, immunomodulatory and lipoprotective effects.…”
Section: Contribution Of Micronutrients To Non‐alcoholic Fatty Liver mentioning
confidence: 99%
“…Non‐alcoholic fatty liver disease patients have been shown to have decreased levels of serum zinc, copper, vitamins A, C, D, E and carotenoids. Moreover, an iron and selenium excess have been reported to play a role in the severity of NAFLD …”
Section: Contribution Of Micronutrients To Non‐alcoholic Fatty Liver mentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD is a systemic disorder of energy, glucose, and lipid homeostasis with hepatic manifestations [3]. Metabolic disorders, such as lipid accumulation, insulin resistance (IR), and inflammation, have been implicated in the pathogenesis of NAFLD, but the underlying mechanisms, including those that drive disease progression, are not fully understood [4].…”
Section: Introductionmentioning
confidence: 99%